A review of the implementation of the CAPS Life Skills curriculum training, as a recontextualising process, in engaging teachers in environmental education in two districts of the Eastern Cape Province - Yoyo, Sindiswa (Rhodes University, Faculty of Education, Department of Education, 2018)
This study examines how the implementation of CAPS Life Skills curriculum training (as a recontextualising process) is engaging teachers in environmental education. The research was centred on training manuals for Life Skills (Official Recontextualisation Field) and their use in CAPS training at district level in two Eastern Cape sites of recontextualisation (Professional Recontextualisation Field). During the training, teachers developed lesson plans that were reviewed and group interviews were conducted on the training process and its outcomes. The manuals, training process, lesson plans and interview transcripts were analysed for evidence of environmental education, notably content, teaching and learning methods and assessment strategies. Bernstein's (1990) framework of the pedagogic device underpins this study. Here the concept of the relay is key for tracking the "relay" of the content, teaching and learning methods and assessment strategies through the processes of recontextualisation into the lesson plans for the field of production. During the process of de-location and relocation, gaps are created and this study sought to track and probe patterns of omissions that took place during the relay process in two cases of training. The review of the in-service training course process of recontextualisation and its cascading approach exposed challenges of omission as it became clear that at each level of the recontextualisation process, gaps were apparent. The study highlighted how the 3-5 day workshop process reviewed was not a robust model for professional development. It was not effective and changes in the mode of delivery and processes of support that reach into curriculum practice in the context of the school are recommended. The study concludes that there is a need for continuous professional development as teachers need ongoing support especially for a "new" curriculum like CAPS that is content driven.
Keywords: Life skills-- Study and teaching (Continuing education) -- South Africa -- Eastern Cape; Environmental education Curricula -- South Africa -- Eastern Cape; Teachers In-service training -- South Africa -- Eastern Cape; Curriculum change -- South Africa -- Eastern Cape; Teachers Education (Continuing education) -- South Africa -- Eastern Cape